Arrhythmias in Pregnancy. Experience of the Multidisciplinary Team - Sergii O. Siromakha; Iuliia V. Davydova; Borys B. Kravchuk; Valerii P. Zalevskiy; Nataliia B. Nakonechna; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2022)
Arrhythmia is the main cause of pregnancy-related hospitalizations. Potential risk of arrhythmias during pregnancy is associated with hypercoagulation and increased risk of thromboembolism.The aim. To increase patients’ safety and to improve maternal and perinatal outcomes by choosing the optimal medical strategy.Methods. We present the experience of multidisciplinary care for 54 pregnant and parturient women (32 with tachy-, 20 with bradyarrhythmia and 2 with ventricular asynchrony) who were admitted to the cardiac surgery facility from December 2013 to February 2022. Pacemakers were implanted in 15 cases of complete atrioventricular block radiofrequency ablation was performed in 12 cases.Results. There were no near misses and maternal losses in our group of patients. Two programmed perinatal losses were provided in patients with rhythm disorders and complex congenital heart defects. Type and place of delivery were chosen by the multidisciplinary team. There were nine childbirths at a specialized cardiac surgery clinic. There were no perinatal losses among patients who underwent rhythm interventions. In our group of patients, electrical cardioversion was performed in three cases, the pregnancies ended successfully with the birth of healthy newborns.Conclusions. Arrhythmias in all trimesters of pregnancy and the postpartum period are a common reason for seeking medical attention and hospitalization during pregnancy.Most of the arrhythmias are hemodynamically insignificant and don’t require hospitalization. Maternal risk stratification of major cardiac events during pregnancy, childbirth and the postpartum period is the cornerstone for choosing a strategy of medical care for pregnant women with arrhythmias. Patients with hemodynamic manifestations of tachy- and bradyarrhythmias, as well as patients with life-threatening types of rhythm disturbances are in the focus of attention of pregnancy heart team. Preconceptional management of patients with life threating arrhythmias is the best type of care in these patients. Pregnancy and delivery in high-risk class patients should be managed in an experienced center with on-site interventional electrophysiology techniques. Rhythm interventions have extremely limited indications and can be conducted when less invasive treatment strategy is unsuccessful.